PENERAPAN MEDIA PAPAN MAGNETIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 5–6 TAHUN - Firdiasari, Yuliana; Supriatna, Asep; Kurniasih, Kurniasih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to improve the symbolic thinking ability of 5–6 year-old children in recognizing letter symbols through the use of magnetic board media at Pos PAUD Arrahman, Pedes District. The subjects were 12 children in group B, consisting of 7 girls and 5 boys. The study applied Classroom Action Research (CAR) in two cycles, each involving planning, action, observation, and reflection. The results showed that in the pre-cycle stage, most children were in the Beginning to Develop category (33%) and Not Yet Developed category (42%). Children generally recognized letters verbally but struggled to identify letter symbols accurately, highlighting the need for concrete learning experiences. In Cycle I, improvements were noted with 50% of children in the Beginning to Develop category and 34% in the Developing as Expected category, though some still had difficulty distinguishing vowels and consonants. In Cycle II, the use of magnetic board media produced significant progress. Most children reached the Developing as Expected (42%) and Very Well-Developed (42%) categories, with a total of 84% surpassing the 75% success indicator. Children were able to recognize letter symbols accurately, relate them to their sounds, and apply this knowledge in learning. These findings demonstrate that magnetic board media is an effective concrete learning tool to enhance symbolic thinking in early childhood. Its interactive and play-based nature suits children’s cognitive development in the preoperational stage and provides multisensory experiences that strengthen symbolic understanding as a foundation for literacy.